2022
DOI: 10.26499/rnh.v11i2.5177
|View full text |Cite
|
Sign up to set email alerts
|

Health Protocol Campaign in The City of Malang as a Covid-19 Pandemic Mitigation: A Study of Linguistic Landscape

Abstract: This study aims to examine the portrait of linguistic landscape (LL) and its social aspects as reflected in the health protocols (Prokes ‘Protokol Kesehatan') banners and billboards in public spaces in Malang. Thus, it attempts to answer two questions: (1) what are the perceptions and attitudes of the people of Malang city towards the various calls for health protocol? and (2) how effective are the calls in impeding the outbreak of Covid-19 in Malang city? According to Backhaus (2006), several important criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Perhaps one of the most important observations to emerge from the data, however, was a bidirectional relationship between CLL and people"s perceptions and behaviors during and after the COVID-19 pandemic. As found in various studies (e.g., Kuße, 2021;Phyak & Sharma, 2022;Rozin, et al, 2022), CLLs reflect people"s thoughts, beliefs and ideologies, these signages have an explicit influence on people"s perceptions, practices, and attitudes as found in this study. This finding is also consistent with previous studies such as Kalocsá nyiová , et al, 2021, Marshall, 2021, Phyak, and Sharma, 2022, Hopkyns and van den Hoven, 2022and Lacsina and Yeh, 2022, that found that outdoor media (LL) can be a powerful tool that serves several functions including being informative, communicative, social, and political.…”
Section: The Influence Of Covid-19 Signs On the Individuals" Daily Ro...supporting
confidence: 81%
See 1 more Smart Citation
“…Perhaps one of the most important observations to emerge from the data, however, was a bidirectional relationship between CLL and people"s perceptions and behaviors during and after the COVID-19 pandemic. As found in various studies (e.g., Kuße, 2021;Phyak & Sharma, 2022;Rozin, et al, 2022), CLLs reflect people"s thoughts, beliefs and ideologies, these signages have an explicit influence on people"s perceptions, practices, and attitudes as found in this study. This finding is also consistent with previous studies such as Kalocsá nyiová , et al, 2021, Marshall, 2021, Phyak, and Sharma, 2022, Hopkyns and van den Hoven, 2022and Lacsina and Yeh, 2022, that found that outdoor media (LL) can be a powerful tool that serves several functions including being informative, communicative, social, and political.…”
Section: The Influence Of Covid-19 Signs On the Individuals" Daily Ro...supporting
confidence: 81%
“…However, despite the ubiquity of COVID-19 research, especially on crisis communication, very limited attention was given to examining the dimensions of the reader's experience and the effect of the LL on readers in sociolinguistics, especially in the LL research field (Lacsina & Yeh, 2022;Rozin, Eka & Setiawan, 2022). Piller et al (2020) claim that only a few studies have dealt with the crisis from a sociolinguistic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Boso Walikan is actually far from complicated. It is a flexible combination between Javanese and Indonesian languages that are spoken in backward formations (Hermawan, 2014;Hoogervorst, 2014;Rozin et al, 2022;Tropea, 2022;Yannuar, 2022). For example, instead of saying kaos kamu apik (your shirt is nice -in a normal sentence formation), Malangese may opt to say soak umak kipa (your shirt is nice -in a backward sentence formation).…”
Section: The Slang Language In Malangmentioning
confidence: 99%